Autism Spectrum Disorder, Language Disorder, and Social (Pragmatic) Communication Disorder: Overlaps, Distinguishing Features, and Clinical Implications. (7th June 2016) - Taylor, Lauren J.; Whitehouse, Andrew J. O.
Abstract : Background: The diagnostic boundaries between autism spectrum disorder (ASD) and specific language impairment (SLI) are not clear‐cut. Evidence of the lack of distinct boundaries between these disorders comes from research identifying a group of children who have pragmatic language difficulties that can be distinguished from those in children with SLI and those with ASD. These findings have led to the inclusion of a new diagnostic category, social (pragmatic) communication disorder (SPCD), in the Diagnostic and Statistical Manual of Mental Disorders‐5th Edition DSM‐5. While this new diagnostic category appears to capture a subgroup of children who may not have been recognised in the DSM‐IV, SPCD has been criticised due to a lack of empirical evidence, showing that the disorder is distinct from ASD in terms of aetiology, intervention, and prognosis. Objective: The purpose of this paper was to summarise the literature that has investigated overlaps in the phenotypes of SLI, ASD, and SPCD. A secondary objective was to present a framework for the assessment and diagnosis of these three conditions. Method and Results: In this paper, we review the research that has examined overlaps in the aetiologies and phenotypes of ASD, SPCD, and SLI. While the results highlighted overlaps in the language profiles and autistic symptomatology, these three conditions could also be distinguished based on the severity of the social communication deficits and the absence of rigid and repetitive behaviour in strictly defined cases of SPCD and SLI. Conclusions: Strictly defined cases of SPCD and SLI can be distinguished from ASD. However, there is a lack of assessment tools that can reliably distinguish these three conditions. We consider the clinical implications of the findings and present a model of assessment and diagnosis for ASD, SLI, and SPCD.